Characterization of the segregating generation of a tomato hybrid carrying nor and exotic genes - Rodríguez, Gustavo; Pratta, Guillermo; Zorzoli, Roxana; Picardi, Liliana Amelia (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to study recombination of the productive and fruit quality traits in the segregating generation of the hybrid between a cultivated variety of Lycopersicon esculentum homozygous for nor and the accession LA1385 of L. esculentum var. cerasiforme using multivariate statistical analysis. F1 and F2 generations and the parents were evaluated for vegetative and productive traits (internode length, stem perimeter at the basal, middle and apical parts, number of flowers per cluster, number of clusters per plant and days to harvest) and quality fruit traits (weight, shape, soluble solids content, acidity, firmness, color and shelf life). A canonical correlation between vegetative and productive traits and those of fruit quality and clustering for fruit traits performed with the F1 and F2 and the parents were used. The productive and fruit quality traits showed recombination in the segregating generation. Shelf life was the most outstanding fruit trait to discriminate groups in the F2. For three cluster levels each group of F2 individuals behaved each one of the parents and the F1.